Comparative Study of Ni Loading Methods Towards Superior CO2 Conversion Over Ni/SBA-15 - N. Bukhari, S.; C. Chong, C.; D. Setiabudi, H.; Ainirazali, N.; A.A. Aziz, M.; P. Teh, L.; H.R. Annuar, N. (International Journal of Engineering and Technology, 2018)
A series of Ni/SBA-15 catalysts were successfully synthesized via conventional wet impregnation method (C-IM), P123-assisted impregnation method (P123-IM) and ultrasonic-assisted impregnation technique (US-IM) methods. The obtained results confirmed that the impregnation methods significantly influenced the physio-chemical properties of Ni/SBA-15 catalysts, which subsequently influenced the catalytic performances of catalysts. The catalytic performance of catalysts followed the order of Ni/SBA-15(P123-IM) > Ni/SBA-15(US-IM) > Ni/SBA-15(C-IM), indicating the superior performance of Ni/SBA-15(P123-IM) towards CO2 methanation (CO2 conv.: 91.1%, CH4 selec.: 97.7%) and CO2 dry reforming (CO2 conv.: 82.6%, H2/CO: 1.23). The excellent catalytic performances of CO2 methanation and CO2 dry reforming over Ni/SBA-15(P123-IM) were owing to its favorable textural properties; homogenous Ni dispersion, smaller NiO crystallite size (12.1 nm), and a higher concentration of metal-support interaction upon the introduction of P123 as the surfactant during the impregnation method. The P123-IM method successfully synthesized the favorable Ni/SBA-15 for superior CO2 conversion and could be used in various applicationsÂ  Â